The moderating effect of resilience on the relationship between academic stress and school adjustment in Korean students - Choi, Sumi; Yoo, Inhwa; Kim, Dongil; An, Sohyun; Sung, Yoonhee; Kim, Changhyun (Frontiers in Psychology, 2023)
Introduction This study investigated the moderating effects of resilience on the relationship between academic stress and school adjustment among Korean adolescents. We examined the moderating effect for the total scores of school adjustment and the two subscales of school adjustment (academic adjustment and general school adjustment). Methods Data were obtained in Pusan, Korea, using the convenience sampling method, and a total of 674 participants' responses were used for the final analysis. Hierarchical regression analysis and multiple regression analysis were performed to examine our research questions. Results The results of the study showed that academic stress was a significant predictor of school adjustment among Korean adolescents. More specifically, academic stress was related to poor school adjustment. The study also found that resilience has a significant mediating effect on the relationship between academic stress and school adjustment. Discussion Our findings suggest that resilience is likely to alleviate the harmful effect of academic stress on school adjustment. Finally, implications for school-based intervention were discussed for providing practical academic assistance.